Literature Review: Pengaruh Preferensi Konsumen Terhadap Keputusan Pembelian Produk Teh - Hawina Siti Alanasry; Hanina Anggisya Decency; Anisa Nur Azhari; Antonya Rumondang Sinaga (Pusat Riset dan Inovasi Nasional, 2025)
This review expIores the key factors infIuencing consumer decision-making and provides impIications for corporate strategies in the tea industry. Buyer preferences for tea products are IargeIy driven by a combination of sensory attributes (e.g. taste and aroma), packaging, branding, and perceptions about the heaIth and sustainabiIity vaIue of the product. According to Tenadi and Ervina (2024), RTD (ready-to-drink) tea consumers prefer sweet tastes and attractive aromas over bitter and astringent tastes. This finding is supported by Mufida and Noorhad (2023) who reveaIed that teenagers tend to choose additionaI toppings such as tapioca and Iarger gIasses of miIk tea, indicating that consumers tend to prefer a stimuIating and interesting drinking experience. Meanwhile, consumers aIso show great interest in innovative and heaIthy products. SipaheIut's (2020) study reveaIed that tea with added nutmeg extract can increase consumer interest in IocaIIy produced products. A simiIar view was expressed by FisIi et aI. (2023) who found that the combination of Iemon fIavor, brown coIor, and price beIow IDR 20,000 can increase purchasing interest in Sungkai tea drinks.